1986
DOI: 10.1212/wnl.36.3.432
|View full text |Cite
|
Sign up to set email alerts
|

Familial amyloidosis with cranial neuropathy and corneal lattice dystrophy

Abstract: A 64-year-old woman had bilateral facial weakness, mild peripheral neuropathy, incoordination, and impaired balance. A corneal transplant had been performed for corneal lattice dystrophy. Sural nerve biopsy showed mild axonal neuropathy with deposits of amyloid in the perineurium. Histochemical studies showed amyloid protein AA in the nerve, but not in cornea or muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…It can be concluded that in this form of AGel amyloidosis, dementia does not appear to be prevalent. Similar was the finding also in the previous study of 31 cases (Kiuru et al, 1995), although dementia has been reported in single patients (Kiuru, Salonen & Haltia, 1999; Darras et al, 1986; Haltia et al, 1991). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It can be concluded that in this form of AGel amyloidosis, dementia does not appear to be prevalent. Similar was the finding also in the previous study of 31 cases (Kiuru et al, 1995), although dementia has been reported in single patients (Kiuru, Salonen & Haltia, 1999; Darras et al, 1986; Haltia et al, 1991). …”
Section: Discussionsupporting
confidence: 92%
“…Histological findings revealed alterations of the white matter and involvement of spinal and cerebral blood vessels and meninges, and slight to moderate diffuse loss of myelin (Kiuru, Salonen & Haltia, 1999). Dementia is reported in single cases (Kiuru, Salonen & Haltia, 1999; Darras et al, 1986; Haltia et al, 1991), potentially related to associated CNS diseases. In the study of 31 AGel patients by Kiuru et al (1995) minor signs of CNS involvement were found in the MRI revealing significantly more frequent high intensity lesions in subcortical and deep white matter, periventricular regions and/or in the pons.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated number of living patients in Finland is about 400-600. Some cases with identical clinical findings have also been reported in the Netherlands, Czechoslovakia, Denmark, the United States, and Japan (Klaus et al, 1959;Winkelman et al, 1971;Boysen et al, 1979;Sack et al, 1981;Purcel et al, 1983;Darras et al, 1986;Sunada et al, 1993).…”
Section: Introductionmentioning
confidence: 77%
“…12 Dysphagia and dysarthria due to bulbar palsy may occur. 12,20 Ataxia has been reported in some patients 3,12 and mild, predominantly sensory, peripheral neuropathy 2,8 as well a carpal tunnel syndrome have also been described. 8,12 The autonomic nervous system is sometimes slightly affected.…”
mentioning
confidence: 99%